Participation and Reasons for Non-participation in Sport and Recreational Activities Before and After the Outbreak of COVID-19: Analysis of Data From the 2016 and 2021 Poland National Sports Participation Survey - Piątkowska Monika; Biernat Elżbieta (Sciendo, 2023)
The ongoing study of factors that hinder physical activity (PA) supports the adaptation of intervention strategies to changing conditions and the creation of a more conducive environment for active lifestyles. The aim of the study was to analyze the barriers to Polish participation in sports and recreational activities (SRA) before and after the pandemic. Face-to-face interviews were conducted twice with a representative sample of Poles (in 2016 N=12183 household members, in 2021 N=8351). Descriptive statistical analysis was conducted using frequency and relative frequency (%). A Chi-square test of independence was used to analyze relationships between perceived barriers of non-participation in sports or physical recreation in 2016 and 2021 and the gender and age of respondents. In 2021, 38.8% (36.7% of women and 41.0% of men) declared participation in SRA (regularly or occasionally), with a 7.6 % point decrease in the number of those active compared to 2016. 20.6% of respondents participated in sports and recreation regularly in 2021. Compared to 2016, (21.7%) the difference was not statistically significant. Men declared regular participation more often than women (23.1% vs. 18.1% - 2021). Four main barriers were identified: (1) lack of free time - especially among 30 to 39-year-olds, 40 to 49-year-olds and men; (2) lack of interest, willingness or preference for passive leisure activities - especially among 15 to 19-year-olds; (3) having a medical condition and doctor's contraindications - among 50 to 59-year-olds and 60 and older; and (4) age - especially among 60-year-olds.